Are farmers willing to enter the forestry property market? Evidence from collective forest areas in southern China - Han, Yaqing; Wang, Qiangqiang; Wei, Yuanzhu (Frontiers in Forests and Global Change, 2023)
The Chinese government encourages farmers to enter the forestry property market for forestry property trading and promotes the standardization of the forestry property trading market. Based on the theory of planned behavior, this paper used the survey data of farmers in collective forest areas in three southern provinces of China to reveal the psychological decision-making process of farmers entering the forestry property market by structural equation model (SEM). The research results show that: (1) Farmers' behavioral attitudes (AB), subjective norms (SN) and perceptual behavioral control (PBC) positively influence farmers' willingness to enter the forestry property market. (2) An important reason why farmers' intentions are largely not effectively translated into behavior is the constraint of PBC. (3) Reducing the risk of transfer and maintaining the interests of both parties constitute the main factors of AB, and the greatest external pressure on farmers' willingness to enter the forestry property market comes from the opinions of village collectives. (4) PBC has a significant impact on behavior, where unfamiliarity with the forestry property market is the main factor affecting farmers' PBC. Therefore, the government should further strengthen the propaganda of forestry property right market, improve the market service system, reduce the transaction cost, introduce specific encouragement policies and measures, and effectively consider farmers' interest demands on forestry property trading; in addition, the power of grassroots organizations should be emphasized when formulating forestry property trading policies.